The Democratic Peace Theory and Its Problems - Munafrizal Manan (Jurnal Ilmiah Hubungan Internasional, 2014)
This essay discusses the democratic peace theory from the prespective of both its proponents and opponents. The puzzle of the democratic peace theory has long been debated methodologically and empirically. Both have a strong argument to support their views, however. This essay highlights the debate by focusing on three problems of the democratic peace theory. First, the differences of the definitions of democracy, war, and peace that demonstrates the lack of robustness in the democratic peace theory. Second, democracy by force has often failed to establish peace whether international or domestic peace and therefore the promotion of democarcy around the world have been seen as a justification of democratic intervention to other sovereign states. Third, the democratic peace theory does not always apply in new emerging democratic countries. As a result, it raises a question whether the democratic peace theory or an ideology.